Research Trends in Physics Learning Strategies: A Systematic Literature Review Addressing Students' Conceptual Understanding Difficulties in Kinematics - Shinta Nuriyah Mahbubiyah Royani; Sutopo Sutopo; Arif Hidayat; Parno Parno (Jurnal Penelitian Pendidikan IPA, 2025)
Conceptual understanding is a basic skill that students need to have in learning. This has encouraged many researchers to implement strategies in learning to improve students' understanding of kinematics material. This article conducts a comprehensive review of 22 Scopus indexed journals to answer research questions related to What strategies are used in learning kinematics material and what difficulties do students experience during learning? The method is carried out using the PRISMA stages which consist of four journal mapping processes, namely identification, screening, eligibility, and included in this review. The review results indicate that from 2016 to 2024, various strategies and comparative studies have been implemented in kinematics learning. Most of these strategies effectively enhance students' conceptual understanding. However, there are still some difficulties for students in understanding the concept of kinematics which are still underlined, especially in understanding the interpretation of x-t, v-t, and a-t graphs.